2021
DOI: 10.1051/0004-6361/202141051
|View full text |Cite
|
Sign up to set email alerts
|

A major asymmetric ice trap in a planet-forming disk

Abstract: Context. The chemistry of planet-forming disks sets the exoplanet atmosphere composition and the prebiotic molecular content. Dust traps are of particular importance as pebble growth and transport are crucial for setting the chemistry where giant planets form. Aims. The asymmetric Oph IRS 48 dust trap located at 60 au radius provides a unique laboratory for studying chemistry in pebbleconcentrated environments in warm Herbig disks with gas-to-dust ratios as low as 0.01. Methods. We use deep ALMA Band 7 line ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Lee et al (2019) reported the detections of CH 3 CHO and CH 3 CN, in addition to CH 3 OH, toward Class I disks around FU Ori-type young star V883 Ori with ALMA. In addition, some of these molecules have been observed toward Class II disks by previous infrared observations (C 2 H 2 ; e.g., Pontoppidan et al 2010) and ALMA observations, such as H 2 CO and CH 3 OH (see, e.g., Loomis et al 2015;Walsh et al 2016Walsh et al , 2018Booth et al 2021a;van der Marel et al 2021;Guzmán et al 2021), and C 3 H 2 , CH 3 CN, HC 3 N, and HCOOH (see, e.g., Qi et al 2013;Öberg et al 2015;Bergner et al 2018;Favre et al 2018;Loomis et al 2018Loomis et al , 2020Ilee et al 2021). Booth et al (2021a) reported the first detection of CH 3 OH in the disk around a Herbig Ae star, HD 100546.…”
Section: Implication For the Observations Of Protoplanetary Disksmentioning
confidence: 83%
See 2 more Smart Citations
“…Lee et al (2019) reported the detections of CH 3 CHO and CH 3 CN, in addition to CH 3 OH, toward Class I disks around FU Ori-type young star V883 Ori with ALMA. In addition, some of these molecules have been observed toward Class II disks by previous infrared observations (C 2 H 2 ; e.g., Pontoppidan et al 2010) and ALMA observations, such as H 2 CO and CH 3 OH (see, e.g., Loomis et al 2015;Walsh et al 2016Walsh et al , 2018Booth et al 2021a;van der Marel et al 2021;Guzmán et al 2021), and C 3 H 2 , CH 3 CN, HC 3 N, and HCOOH (see, e.g., Qi et al 2013;Öberg et al 2015;Bergner et al 2018;Favre et al 2018;Loomis et al 2018Loomis et al , 2020Ilee et al 2021). Booth et al (2021a) reported the first detection of CH 3 OH in the disk around a Herbig Ae star, HD 100546.…”
Section: Implication For the Observations Of Protoplanetary Disksmentioning
confidence: 83%
“…They showed that the gas-phase molecular abundances of such as H 2 O and CH 3 OH are enhanced in the warm surface layer due to the effects of vertical mixing. van der Marel et al (2021) discussed that this vertical transport may be important to explain the observed abundance of CH 3 OH in the disk around IRS 48, in addition to icy dust concentrations at the dust trap. In addition, we assume that the disk physical structure is steady and that the shadow structure is maintained for 10 6 yr. We note that the inward migration of solids and/or destruction of the shadow structure after the efficient formation of CH 3 OH ice in the shadowed region may increase the abundances of various complex organic molecules in the inner disks around the water snowline (see also Section 4.2).…”
Section: Other Model Caveatsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, high resolution observations with ALMA have enabled comparisons between dust asymmetries and molecular gas at small spatial scales. While a number of studies have drawn tentative links betwen dust and gas substructures (Law et al, 2021;Zhang et al, 2021;Guzmán et al, 2021;Alarcón et al, 2021;Ilee et al, 2021;van der Marel et al, 2021), intriguingly there is often no clear connection to be made. Furthermore, asymmetries seen in a particular species within a particular disk are often not observed in other species, or even within different transitions of the same species.…”
Section: Discussionmentioning
confidence: 99%
“…12 Although with more difficulty, CH 3 OH has been detected in protoplanetary disks, the next stage of stellar evolution which directly precedes the formation of a planetary system, thereby demonstrating that methanol, and consequently larger iCOMs, are present at the planet formation stage. [13][14][15][16][17] CH 3 OH has been detected as a volatile species in several comets, including 67P/Churyumov-Gerasimenko by the recently concluded Rosetta mission, [18][19][20] as ice on the surface of a Kuiper Belt Object (KBO) 21 and it is among the few iCOMs detected in other galaxies. 22 Chemical modelling, experimental determinations and astronomical observations [23][24][25] have clearly established that methanol observed in regions of star formation is synthesized by successive hydrogenation of CO-rich ice mantles.…”
Section: Introductionmentioning
confidence: 99%